Atrial fibrillation, liver disease, antithrombotics and risk of cerebrovascular events: A population-based cohort study. (15th November 2016) - Lai, Hui-Chin; Chien, Wu-Chien; Chung, Chi-Hsiang; Lee, Wen-Lieng; Wu, Tsu-Juey; Wang, Kuo-Yang; Liu, Chia-Ning; Liu, Tsun-Jui
Abstract: Background: Whether patients with atrial fibrillation (AF) and liver disease are also prone to cerebrovascular events and respond similarly favorably to antithrombotic therapy remains under-investigated. Methods: Patients ≥ 18 years with newly-diagnosed AF in the period 2005 to 2009 were scrutinized from the "Longitudinal Health Insurance Database 2005" (1 million beneficiaries) of Taiwan's National Health Insurance Institute. Patients were categorized into the Liver ( N  = 433) or the Non-liver ( N  = 3490) cohort according to whether they had a diagnosis of advanced liver disease. Patients were then followed to determine cumulative incidence of hospitalization-requiring cerebrovascular events, preventive effects of antithrombotics, and predictors of cerebrovascular events by Cox regression analysis. Results: Within a mean follow-up of 3.3 ± 1.4 years, ischemic stroke (89.2 vs. 50.3 per 1000 person-years, adjusted HR 1.502, 95% CI 1.207–1.868, p  < 0.001) and overall cerebrovascular events (102.3 vs. 56.4 per 1000 person-years, adjusted HR 1.535, 95% CI 1.251–1.883, p  < 0.001) occurred significantly more often in the Liver than in the Non-liver cohort. Cox models identified aging (≥ 65 years), DM, and CHA2DS-VASc score ≥ 2 points as risk factors for overall cerebrovascular events in the Liver cohort, whereas antiplatelet agents (HR 0.932, 95% CI 0.128–6.803, p  = NS) and vit-K antagonistic anticoagulants (HR 1.087, 95% CI 0.150–7.862, p  = NS) showed no correlation. Conclusion: AF patients comorbid with advanced liver disease are more vulnerable to ischemic and therein overall cerebrovascular events, especially in those with old age, DM, or high CHA2DS-VASc scores. This propensity to cerebrovascular events, however, can't be altered by antithrombotic therapy.